2016
DOI: 10.32728/ric.2016.21/1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of University Students’ Efl Writing Apprehension: A Longitudinal Study in Croatia

Abstract: Writing apprehension defines a person's ability to write under various stress types. Depending on a situation, an average person might perform below expectations, or be less apprehensive about writing than a professional. The purpose of this research is to investigate Croatian University students' English as a foreign language writing apprehension. For the purpose to determine if the variables of students' gender and academic level (age) play a role in their writing apprehension, we adapted WAT (Writing Appreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 2 publications
2
9
1
Order By: Relevance
“…Most of the studies that belong to the second set are among the ones that have been carried out among non-native writers of English whose high apprehension of their females in writing ascribes to the dominant role of men, females' hypersensitivity to negative evaluation, appropriation of voice, and education in the context of those studies. Nevertheless, our finding is confirmed in the literature by a number of studies that detected no significant differences (Abu Shawish & Abdelraheem, 2010;Al Asmari, 2013;Kostić-Bobanović, 2016;Popvich & Masse, 2005;Zerey, 2013).…”
Section: The Effect Of the Variables On Writing Apprehensionsupporting
confidence: 89%
See 4 more Smart Citations
“…Most of the studies that belong to the second set are among the ones that have been carried out among non-native writers of English whose high apprehension of their females in writing ascribes to the dominant role of men, females' hypersensitivity to negative evaluation, appropriation of voice, and education in the context of those studies. Nevertheless, our finding is confirmed in the literature by a number of studies that detected no significant differences (Abu Shawish & Abdelraheem, 2010;Al Asmari, 2013;Kostić-Bobanović, 2016;Popvich & Masse, 2005;Zerey, 2013).…”
Section: The Effect Of the Variables On Writing Apprehensionsupporting
confidence: 89%
“…Yet inconsistently, other research observed no statistically significant differences between males and females in writing apprehension. A recent longitudinal study by Kostić-Bobanović (2016) showed that gender did not have any role in writing apprehension among Croatian EFL undergraduate students neither in their first year nor in their third year. He thought that the causes that make them feel anxious in writing seem to be the same.…”
Section: Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations